Penerapan Model Pembelajaran PjBL untuk Meningkatkan Pemahaman Konsep Perubahan Wujud Benda pada Siswa Sekolah Dasar - Septiana Hadisah; Ibnu Muthi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the application of the Project Based Learning (PJBL) learning model in improving the understanding of the concept of changes in the state of matter in Elementary School students. The background of this study is based on the low understanding of students on the material of changes in the state of matter, which can have an impact on the weak mastery of scientific concepts as a whole. The method used is qualitative research with a library research approach, where data is collected through analysis of various scientific literature, journals, and relevant academic sources. The results of the study indicate that PJBL is a learning model that emphasizes the active involvement of students in real projects, from designing, implementing, to presenting the results. The application of PJBL in the topic of changes in the state of matter encourages students to experience scientific processes such as melting, evaporating, freezing, and condensing directly through simple experiments. PJBL not only improves students' conceptual understanding, but also develops science process skills, critical thinking, collaboration, communication, and responsibility. In its implementation, PJBL follows certain stages starting from determining essential questions to reflection. Despite facing several challenges such as limited time, facilities, and teacher readiness, solutions can be sought through effective planning and professional training. Thus, PJBL has proven to be the right approach in improving the quality of science learning in elementary schools, especially in strengthening students' understanding of the concept of changes in the state of objects in a comprehensive and meaningful manner.